FACTORS ASSOCIATED WITH UPPER LIMB FUNCTIONAL RECOVERY IN STROKE PATIENTS TREATED WITH COMBINED FUNCTIONAL ELECTRICAL STIMULATION AND OCCUPATIONAL THERAPY AT BACH MAI HOSPITAL (Vietnam Journal of Community Medicine, 2026)
Objective: To evaluate the outcome of upper limb rehabilitation in stroke patients using combined functional electrical stimulation (FES) and occupational therapy, and to identify factors associated with functional improvement.Methods: A prospective one-group pre–post intervention study was conducted at the Rehabilitation Center of Bach Mai Hospital in 2025 on 90 stroke patients who met the inclusion criteria. All patients underwent upper limb rehabilitation with combined FES and occupational therapy for 4 consecutive weeks. Outcomes were assessed before and after the intervention using the Action Research Arm Test (ARAT), Fugl-Meyer Assessment (FMA), and the Barthel Index. Patient factors including age, sex, hemiplegic side, stroke type, time from stroke onset to intervention, and baseline stroke severity (National Institutes of Health Stroke Scale – NIHSS) were analyzed for their association with the degree of functional improvement.Results: After 4 weeks of intervention, the mean ARAT, FMA, and Barthel scores of patients increased significantly compared to baseline (p < 0.001). Patients younger than 60 years, those who received intervention within the first month post-stroke, those with ischemic stroke, and those with milder initial impairment (lower NIHSS) showed significantly greater improvements in upper limb function. There were no significant differences in improvement based on sex or the affected side.Conclusion: The combination of FES and occupational therapy markedly improves upper limb function in stroke patients. Better recovery was observed in patients who were younger, received early intervention, had ischemic stroke, and had mild initial deficits. These findings underscore the importance of early rehabilitation and consideration of prognostic factors in post-stroke rehabilitation planning.
Keywords: Stroke; upper limb rehabilitation; functional electrical stimulation; occupational therapy; prognostic factors; functional recovery.